Implementasi Metode Fuzzy Terhadap Persediaan Pupuk Urea Menggunakan Fuzzy Mamdani - Sitinjak, Yuli Artha Andriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The fertilizer supply system used at the Majalengka Agriculture Service office is still carried out using Microsoft Excel so that the process is too slow and also less effective to be applied at this time. Due to the problems faced by the Majalengka Agricultural Service office in the supply of fertilizer, the author wants to design a data processing system using a programming language, namely the Fuzzy method, as the report media in designing a fertilizer inventory information system at the Majalengka Agriculture office. In designing a fertilizer inventory information system, there are several reports generated from the program that have been designed, such as the fertilizer unit report and the fertilizer stock report at the Majalengka Agriculture office. Therefore, the author hopes that the difficulties encountered can be resolved appropriately and by using the fuzzy method